Analysis of Visibility and Accessibility of the International Test Center (ITC) as a Foreign Language Test Center at Manado State Polytechnic - Lagarens, Yollanda; Tombeg, Beldie A.; Kaligis, Stevie; Samehe, Valen (Perkumpulan Psikologi Transformasi Indonesia (P2TI), 2025)
In the era of Education 5.0, education focuses on holistic human development by utilizing technology to create personalized and adaptive learning experiences and prepare students to face global challenges. Foreign language skills are becoming increasingly important as core competencies that support international mobility and cross-cultural collaboration. Foreign language tests serve as an evaluation tool to measure individual language skills, ensuring graduates can compete in the global market. This study aims to analyze the visibility and accessibility of the International Test Center (ITC) as a foreign language test center at the Manado State Polytechnic. The main focus of the study includes an evaluation of geographical distribution, transportation infrastructure, facilities provided, and test takers' perceptions of the ease and efficiency of services. The research method used is qualitative, including location surveys, interviews, participant observation, and document analysis. Qualitative data were obtained through interviews with institutional leaders, test implementers, partners, participants, and direct observation at the language center location. The study results indicate that the International Test Center has great potential to become one of the best foreign language test centers in North Sulawesi. However, there are still challenges regarding transportation accessibility and participant perceptions of service efficiency. The implications of this research are expected to be the basis for further development for ITC to increase the visibility, accessibility, and quality of its services as a center of excellence for foreign language testing at Manado State Polytechnic.